Value preferences and requirements of the students attending the regional boarding secondary schools - Sibel Yazıcı; Nuray Kurtdede Fidan (Institute of Advanced Engineering and Science, 2020)
The aim of the study was to reveal the preferences and requirements of the students attending the Regional Boarding Secondary Schools (YBO) concerning the values contain in the educational program of the social studies course. The study was designed within the framework of phenomenology which is among the qualitative research methods. The participants of the study are 79 eight grade students attending a regional boarding secondary school in the Turkey. The data of the study are collected through a survey questionnaire with two parts which contains open-ended items. The data were analysed using the descriptive and content analyses. The findings of the study show that the participants do not differ based on gender and the socio-economic background of their families. The frequently preferred values by the participants are found to be attaching importance to the family unity, honesty, sympathy and patriotism. Another finding is that the participants do not provide a clear justification for each of the values they preferred. This suggests that it is difficult to establish a justification for the value. However, requirements value justifications are analyzed, it is seen that students they express the definition of value, its importance and the expectations of having this specific value.